Agriculture-independent, sustainable, fail-safe and efficient food production by autotrophic single-cell protein - Bogdahn,Ingvar (PeerJ PrePrints, 2015)
Food production with plants consumes large amounts of water, occupies large areas of land and cannot guarantee food security beyond the 21st century. Industrial agriculture in particular, is destructive to the environment, fosters climate change in profound ways, deteriorates public health and causes high ”hidden costs”. Single-cell protein (SCP) represents an alternative with minimal carbon-, water- and land footprints. However, when grown on biowastes of industrial agriculture, heterotrophic SCP does not truly improve sustainability or food security. This hypothesis paper proposes autotrophic SCP bioprocess designs which enable sustainable, fail-safe and efficient production of edible biomass from CO2 and N2 or NH3. They can be driven by H2, CO or HCOOH from several sustainable sources. Besides H2O-electrolysis and syngas, surprisingly fossil fuel may provide an effectively carbon-negative and cheap supply of H2 through the decomposition of CH4 or oil. Most promising bioprocess designs consist of 2-stages. In the first stage, homoacetogenic bacteria fix CO2 up to 10 more efficiently than plants, and secrete it as acetate. In the second stage, selected microbes grow on the acetate and thereby form edible biomass. Bacteria have unique features including N2-fixation, H2S tolerance and O2-tolerant hydrogenases for fast light-independent growth. Eukaryotic microalgae are already approved as food and exhibit oxygenic photosynthesis which partly replaces solar-panels, seawater desalination and H2O-electrolyzers. Photoheterotrophic growth on acetate decouples these benefits from inefficient endogenous CO2 fixation. Slow gas mass-transfer, poor light distribution and expensive cell harvest are major challenges arising from the cultivation in liquid media. To cope with this, microbes grow as hydrated biofilms that are exposed directly to substrate gases, and that can be dry-harvested. Two suitable bioreactors are presented and adaptations for 2-stage designs are proposed. Since provision with substrates is expensive, two strategies are proposed for the safe extraction of substrates from food-grade as well as non-food- grade biowastes via partial anaerobic digestion. Additionally, alkalic pH and hydroxides formed at the cathode during electrolysis may be used to precipitate CO2 from the air as carbonates. In two use cases, 2-stage designs with solar-powered H2-generation from seawater were estimated to exceed productivity of wheat 20-200 fold, for moderate and arid climates respectively. Preliminary cost estimates and data about direct and indirect subsidies of industrial agriculture lead to the hypothesis that autotrophic SCP likely outperforms industrial agriculture not only in ecological but also in economical aspects.
Keywords: single-cell-protein; autotrophic; anaerobic digestion; homoacetogenic bacteria; photoheterotrophic; microalgae; acetate; industrial agriculture